THE EFFECT OF READING ATTITUDE TOWARD STUDENTS’ READING COMPREHENSION AT THE EIGHTH GRADE OF SMP NEGERI 2 BAUBAU - Asti Wahyuni B; Yuyu Yuyu (English Education Journal, 2020)
The objective of this research was to find out the effect of reading attitude toward students’ reading comprehension at the eighth grade of SMP Negeri 2 Baubau. This research used a quantitative approach by applying ex-post facto method of causal comparative design. The population of this research was all the eighth grade students of SMP Negeri 2 Baubau with the number was 320 students. The sample of this research was 30 students who were selected using cluster random sampling technique. The instruments of this research were questionnaire and test. The study results showed that the R score was 0.436 categorized in the moderate category. This means that a positive and moderate correlation existed between the reading attitude and the reading understanding of students. Besides, the score of Fcount was 6.559 with the significant value was 0.016. Because the score Fcount was greater than Ftable (4.18) and the score of significance was lower than α (0.05), it meant that null hypothesis was rejected and alternative hypothesis was accepted. So, based on the finding of research and data analysis, it could be concluded that there was significant influence between reading attitude and students’ reading comprehension at the eighth grade of SMP Negeri 2 Baubau.